The Role of Local Creativity in Developing the Competitiveness of Ciwaringin Hand-Written Batik - Fiqih, Muhammad; Yuniarto, Bambang; Sururi, Ahmad (CV. Strata Persada Academia, 2025)
This study explores the role of local creativity in enhancing the competitiveness of Ciwaringin hand-written batik, a traditional Indonesian craft facing increasing challenges from mass-produced textiles and printed batik. Local creativity, encompassing unique design development, eco-friendly material utilization, and innovative marketing strategies, is recognized as a key driver of cultural preservation and economic growth within the creative industry. Employing a qualitative conceptual approach based on an extensive literature review, this research synthesizes theories and empirical findings from reputable sources to construct a comprehensive framework on how local creativity contributes to the resilience and differentiation of Ciwaringin batik in both local and global markets. The findings highlight that local creativity not only strengthens cultural identity but also serves as an adaptive and proactive strategy to meet contemporary consumer demands, particularly among younger generations who value authenticity and sustainability. Innovations in motif design, natural dyeing techniques, and digital marketing platforms collectively form an ecosystem that enhances market visibility and competitiveness. This study recommends structured capacity-building programs, cross-generational collaboration, and supportive public policies to ensure sustainable raw material supply chains and market expansion. Further research is suggested to examine the role of digital technologies, e-commerce models, and creative economy ecosystems in advancing the long-term sustainability and global positioning of traditional batik industries.